2005
DOI: 10.1111/j.1475-2743.2005.tb00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and sulphur management: challenges for organic sources in temperate agricultural systems

Abstract: Abstract. A current global trend towards intensification or specialization of agricultural enterprises has been accompanied by increasing public awareness of associated environmental consequences. Air and water pollution from losses of nutrients, such as nitrogen (N) and sulphur (S), are a major concern. Governments have initiated extensive regulatory frameworks, including various land use policies, in an attempt to control or reduce the losses. This paper presents an overview of critical input and loss proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 114 publications
0
22
0
1
Order By: Relevance
“…Furthermore, plant tissue mineral content differed strongly among soil fertility treatments, which may have caused the differences in larval performance. Given that an increasing number of farmers are using organic farming methods (Willer and Kilcher 2011), and that sulfur and microminerals are becoming increasingly deÞcient in soils worldwide (McNeill et al 2005), it is worthwhile that future studies expand the Ca:Mg:K ratio concept to consider the effects that manure and gypsum additions have on sulfur and micromineral content, and subsequent responses of crop plant mineral nutrition and insect herbivore response.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, plant tissue mineral content differed strongly among soil fertility treatments, which may have caused the differences in larval performance. Given that an increasing number of farmers are using organic farming methods (Willer and Kilcher 2011), and that sulfur and microminerals are becoming increasingly deÞcient in soils worldwide (McNeill et al 2005), it is worthwhile that future studies expand the Ca:Mg:K ratio concept to consider the effects that manure and gypsum additions have on sulfur and micromineral content, and subsequent responses of crop plant mineral nutrition and insect herbivore response.…”
Section: Discussionmentioning
confidence: 99%
“…(2010) has reported ammonia volatilization was 5–16 percent of the N content of residues when placed on top of the soil. McNeill et al. (2005) has indicated that besides leaching of N in the form of nitrate from elevated areas of land, substantial emissions of N as ammonia are also associated with land spreading of residues and manures.…”
Section: Resultsmentioning
confidence: 99%
“…Agriculture has undergone drastic changes over the last few decades, and farms have increasingly become more specialized and more intensive, with arable production often being concentrated in different regions of a country ( McNeill et al., 2005 ). Agricultural activities (e.g., deforestation, burning, plowing, and intensive grazing) and expansions contribute substantially to the carbon pool ( Lal and Kimble, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of N fertilizer applications can drive soil acidification (e.g. Mahler & Harder, ; Bolan et al ., ; Juo et al ., ; McNeill et al ., ; Guo et al ., ). Guo et al .…”
Section: Discussionmentioning
confidence: 99%